Design of an SDR-Based ILS Receiver Tester for Performance Verification - Toni; Sulaiman, Muhammad Arif; Wildan, Muh (Universitas Muhammadiyah Surakarta, 2025)
The ILS receiver must be tested to ensure its reliability. Commercial ILS receiver testers are prohibitively expensive. This study presents one of the first implementations of a functional portable ILS signal generator, utilizing a low-cost alternative with the HackRF One SDR and GNU Radio to generate precise ILS signals as input to the ILS receiver. The research features adjustable DDM/SDM parameters and a GUI interface. Testing with Thales 7010 showed maximum deviations of 0.0011 DDM (Localizer) and 0.0006 DDM (Glide Path), within operational tolerances. The GNU Radio block contains audio components to generate ILS DDM, including 90 Hz and 150 Hz, as well as processing blocks that prepare them for transmission via the HackRF One. Before evaluation, the research was calibrated with the ILS Analyzer Thales 7010. Testing with Thales 7010 showed maximum deviations of 0.0011 DDM (Localizer) and 0.0006 DDM (Glide Path), with SDM at ±40% (Localizer) and ±81% (Glide Path), within operational tolerances. As part of the verification, IFR-4000 was used to confirm the system's viability for receiver testing.